Sedimentology, petrography, and carbon isotopes of the ∼ 2.2 Ga Kona Dolomite, Upper Peninsula of Michigan - Maya L. Giannecchini; Garrett D. Brown; Cory M. Redman; Ian Z. Winkelstern; Dylan T. Wilmeth (Precambrian Research, 2026)

Sedimentology, petrography, and carbon isotopes of the ∼2.2 Ga Randville Dolomite, Upper Peninsula of Michigan - Garrett D. Brown; Maya L. Giannecchini; Cory M. Redman; Ian Z. Winkelstern; Dylan T. Wilmeth (Precambrian Research, 2025)

Territorial and occupancy behavior of black sea bass on oyster aquaculture gear and boulder habitat - Adam D. Armbruster; Renee Mercaldo-Allen; Julie M. Rose; Kristen Seda; Paul Clark; Gillian Phillips; Dylan Redman; Christian W. Conroy (Frontiers in Marine Science, 2024)
Observations of fish behavior can provide insights into habitat preferences and use. Black sea bass, Centropristis striata , are a territorial temperate reef finfish species known for their high commercial and recreational value and association with structured habitat. We used underwater action cameras to record video of black sea bass to assess territorial (agonistic, ambush, displacement) and occupancy (station-keeping) behaviors on shelf and bag style oyster aquaculture cages at a shellfish farm, and on boulders at a natural rock reef near Milford, Connecticut in Long Island Sound, Northwest Atlantic. Black sea bass at a variety of life stages were highly associated with cages, including young-of-the-year, and age 1+ fish. The high abundance of black sea bass observed on cages relative to boulders suggests this species has an affinity for the vertical structure created by aquaculture gear. When behaviors were normalized to the total fish sightings, black sea bass showed no significant difference in frequency of behaviors between habitats, indicating that per-fish rates of behavior were similar on cages and boulders. Demonstration of territorial and occupancy behaviors by black sea bass on, and around cages suggests that aquaculture gear provides structured habitat and ecosystem services for this species similar to natural reefs.These results suggest that essential fish habitat descriptions of manmade structures used by black sea bass could be broadened to include aquaculture gear. Our study provides novel information on behavioral interactions of black sea bass with oyster cages that may support aquaculture permitting and consultation processes.

Oyster aquaculture cages provide fish habitat similar to natural structure with minimal differences based on farm location - Renee Mercaldo-Allen; Peter J. Auster; Paul Clark; Mark S. Dixon; Erick Estela; Yuan Liu; Lisa Milke; Gillian Phillips; Dylan Redman; Barry C. Smith; Alison Verkade; Julie M. Rose (Frontiers in Marine Science, 2023)
Oyster aquaculture gear may augment natural seafloor by providing structured habitat for economically important fish species. Underwater video census was used to assess fish abundance and community composition on eastern oyster ( Crassostrea virginica ) shelf and bag style aquaculture off-bottom cages and within natural rock reef habitat. During 2018, underwater cameras were mounted on four study cages at a dense shellfish farm of 40-100 commercial cages (dense cage farm), on four single cages interspersed on low relief seafloor (sparse cage farm), and amongst four boulders on a rock reef (rock reef), within an embayment off Milford, Connecticut, which is part of Long Island Sound, in the United States. In 2019, cameras were similarly deployed on two study cages per farm at each of three shellfish farms off Milford, Norwalk and Westport, CT. Video was recorded hourly in eight-minute segments from 7 am to 7 pm. Data loggers monitored seawater temperature, light intensity, and current speed. Fish abundance (MaxN) was calculated for all videos. We compared fish abundance and community composition between May and September, on cage and boulder habitat, on cages at dense and sparse farms and on cages across farm locations. In 2018, abundance of black sea bass ( Centropristis striata ), scup ( Stenotomus chrysops ) and tautog ( Tautoga onitis ) was significantly higher on cages than boulders, regardless of cage number. Cunner ( Tautogolabrus adspersus ) abundance was significantly higher on boulders than cages when cage sites were grouped. However pairwise comparisons indicated that cunner were significantly higher at the sparse cage farm versus the rock reef but cunner abundance on the dense cage farm and rock reef sites was not significantly different. Abundance of black sea bass, scup, tautog, and cunner were not significantly different across 2019 farm locations. Young-of-the-year fish occurred episodically at all sites during both years, with black sea bass and scup most abundant. Fish abundance corresponded to seasonal changes in seawater temperature and was highest at the warmest temperatures. Light intensity and current speed explained less variation in fish abundance relative to temperature, and relationships were inconsistent across habitats and farm locations Our results suggest that multi-tiered oyster aquaculture cages contribute structure to seafloor environments that provide habitat for temperate reef fish similar to natural rock reefs.